Contract Specificity, Contract Violation, and Relationship Performance in International Buyer–Supplier Relationships. Issue 3 (September 2015) - Griffith, David A.; Zhao, Yanhui
This work examines contractual governance in international buyer–supplier relationships by investigating the linkages between contract specificity, contract violation, and relationship performance as well as the roles of contract monitoring and a country's institutional factors (i.e., country business risk and country globalization). The findings, based on a survey of international buyer–supplier relationships, provide new insights into a contract specificity → contract violation → relationship performance model. For example, the results indicate that contract specificity is not directly related to contract violation but, rather, that country-level factors moderate the effectiveness of contract specificity (i.e., contract specificity is more effective in suppressing an international buyer's contract violation if the buyer is from a country characterized by low business risk or high country globalization). The results also demonstrate that contract monitoring can mitigate the negative association between contract violation and relationship performance.